2003
DOI: 10.1097/00126097-200312000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The use of peridialysis blood pressure and intradialytic blood pressure changes in the prediction of interdialytic blood pressure in haemodialysis patients

Abstract: These data demonstrate that peridialysis blood pressure values are of limited accuracy in predicting interdialytic blood pressure, post-dialysis values are minimally better predictors than pre-dialysis blood pressures, and the average of pre- and post-haemodialysis values is marginally better than both. In addition, blood pressure fluctuations during dialysis have a sizable impact on this predictive ability. Clinical decisions related to blood pressure management and research design in haemodialysis hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…Furthermore, evidence from prior studies is limited by utilization of case-control designs or regression models that assume a linear relationship between BP change and mortality. 1520 These studies may have been underpowered in detecting a U-shaped association (ie, high mortality with both increases and decreases in BP). We hypothesized that both increases and decreases in BP during HD (defined as post-HD BP minus pre-HD BP) are associated with increased all-cause and cardiovascular mortality independent of pre-HD BP levels.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence from prior studies is limited by utilization of case-control designs or regression models that assume a linear relationship between BP change and mortality. 1520 These studies may have been underpowered in detecting a U-shaped association (ie, high mortality with both increases and decreases in BP). We hypothesized that both increases and decreases in BP during HD (defined as post-HD BP minus pre-HD BP) are associated with increased all-cause and cardiovascular mortality independent of pre-HD BP levels.…”
Section: Introductionmentioning
confidence: 99%
“…Postdialysis rather than predialysis BP was found to be independently related to increased mortality. 18,19 Since the development and clinical application of ambulatory BP monitoring (ABPM), various studies have shown that assessing the circadian BP profile is more predictive than office BP readings in estimating cardiovascular risk. [20][21][22] ABPM has been generally considered as the most accurate method for evaluating BP overload in the general population as well as in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic ABPM was modeled as the dependent variable against age, sex, race, predialysis and postdialysis BP. The average systolic ABPM was related to the dependent variables by the following relationship: 33.74 + 0.13 Â age + 0.66 (average of predialysis and postdialysis systolic [15] studied 60 hemodialysis patients with interdialytic ABPM and dialysis unit BP measured in a standardized manner using auscultatory or oscillometric techniques before and after dialysis. They noted modest correlation of 0.52 between predialysis and ABPM and 0.61 between postdialysis BP and ABPM.…”
Section: Discussionmentioning
confidence: 99%
“…Our population was larger, had predialysis and postdialysis BP recorded by the routine methods as measured by Coomer et al [14], and using standardized methods used by Mendes et al [15]. We used the average of six predialysis and postdialysis BPs instead of using only two.…”
Section: Discussionmentioning
confidence: 99%